Characterising the performance of cache–aware placement of virtual machines on a multi–core architecture. (31st July 2012) - Emeneker, Wesley; Apon, Amy
Virtual machine acceptance and deployment has exploded with the advent of cloud computing. Unfortunately, virtual machines negatively impact application performance. For parallel scientific codes, any negative performance impact is undesirable. This paper presents an initial investigation of performance–impacting machine–level events, comparing the Xen virtual machine to native Linux, and using knowledge of the underlying CPU cache architecture to improve relevant cache behaviour. Several machine–level events are gathered, including translation lookaside buffer misses and cache misses. Results from the experiments show that cache–aware virtual machine placement has a significant impact on scientific applications.